The Influence of Soil Characteristics on the Bearing Capacity of Shallow Foundations - Ismail Nur Ariyanto (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Shallow foundations in heterogeneous soil regions such as Sumatra are vulnerable to bearing capacity failure when key soil parameters are inaccurately determined. This study analyzes the influence of cohesion (c), internal friction angle (φ), and soil unit weight (γ) on the ultimate bearing capacity of shallow square foundations using the Terzaghi equation. A quantitative descriptive approach was applied, substituting purposive laboratory samples—c (0–50 kN/m²), φ (0°–40°), γ (16–20 kN/m³)—into the Terzaghi formula for a square footing (B = 1.5 m, D_f = 1.0 m) with a safety factor of 3. Results show that cohesion and friction angle dominate bearing capacity, yielding q_u = 643.2 kN/m² and q_a = 214.4 kN/m² for the reference case. Accurate laboratory parameter testing is essential for safe, efficient shallow foundation design in variable soil conditions.